(1024) The Projection of Total Expenditure of Private Households in the A.R.E till 1980 توقعات إجمالي إنفاق الأسر الخاص في جمهورية مصر العربية حتى عام 1980 - Hans Waschkau. (INP., 2020)
National planning as it is taken in the socialists countries aims exclusively at rising the standard of living of the people. All planning activities and in general al economic activities are being done for the benefit of the country and its inhabitant. Accepting this starting point the planning of the people` welfare ought to be highlighted to national planning. Following from that planning of individual consumption has to be considered more and less the first step of national planning.